PENETAPAN KADAR FLAVONOID PADA PELEPAH PISANG RAJA (Musa acuminata Colla. forma cerifera Back.) DENGAN VARIASI LAMA WAKTU EKSTRAKSI - Praptanti Sinung Adi Nugroho; Danang Muhammad Sholihin; Aptika Oktaviana Trisna Dewi (Program Studi D3 Farmasi Politeknik Indonusa Surakarta, 2020)
Indonesia is one of the banana exporting countries. There are so many kinds of bananas, one of which is plantain. Plantain contains several ingredients such as flavonoids which have several properties including antioxidants and antimicrobial activity. This study aims to determine the levels of flavonoids in the ethanol extract of plantain stalks with variations in extraction time. The method used was experimental research with three groups of plant extraction treatments, namely extraction time of 2, 3, and 5 days. The extraction method uses maceration with 70% ethanol solvent. Flavonoid levels were obtained using the UV-Vis spectrophotometric method. The yield of extracted results obtained for the duration of 2, 3, and 5 days was 9.97% respectively; 12.62% and 14.14% with average levels of flavonoids obtained respectively 2.69 mg / gram; 5.10 mg / gram and 8.82 mg / gram